COMPARISON OF JUVENILE CRIMINAL JUSTICE SYSTEMS IN AUSTRALIA, INDONESIA AND MALAYSIA - Gemici, Gizandra Indah; Hamidah Abdurrachman; Ramadhani, Deaf Wahyuni (AKADEMI TEKNIK ADI KARYA, 2024)
Child delinquency or juvenile delinquency, which is currently continuing to spread due to rapid changes in times, has made a country create written regulations that are valid in the eyes of the law which contain rules regarding legal violations committed by minors in accordance with the guidelines they regularly use. considering the rights of children as the nation's next generation who do not yet have emotional stability. This article aims to find out how the juvenile criminal justice system is in Australia, Indonesia and Malaysia using the literature study method. The results of the analysis obtained in this article are that the juvenile criminal justice system in Australia has a different legal basis in each state or territory. Meanwhile, Indonesia and Malaysia have the same legal basis throughout their territories. Where Indonesia is based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Malaysia is based on the 2001 Children and Adolescents Law. The types of criminal punishment for children in Australia, Indonesia and Malaysia both prioritize rehabilitative actions with the aim of improving character. and to ensure they can return to society armed with better skills and a positive attitude